Implementation of e-rental housing via generic notification message through mobile phone / Suzana Ahmad, Norzehan Sakamat and Noorazida Mohd Idris - Ahmad, Suzana; Sakamat, Norzehan; Mohd Idris, Noorazida (Research Management Institute (RMI), 2009)
As UiTM increases its student enrollment, the number of students seeking accommodation inherently increases. This is particularly true with respect to off-campus accommodation since the number of students that the residential colleges can accommodate is limited. Unit Kebajikan NR (Non Resident) under Hal Ehwal Pelajar (HEP) has been set up to assist students looking for suitable accommodation. The unit is still implementing a manual- and paper-based processing to capture information. This is both highly inefficient and time consuming. This study provides a convenient platform for students and landlords to share updated information about available rental accommodation. A prototype web-based rental housing system, which is based on generic notification messaging, has been developed. This online system offers services to students seeking rental accommodation around the UiTM campus. Home owners can use this system to advertise their properties without the use of paper based forms or placing advertisements in newspapers, which is common practice. Communication between potential landlords and tenants can be done interactively via SMS once both parties have registered with the system. A System Development Life Cycle (SDLC), an iterative development, has been adopted for the purposes of evaluating this study. This research has the potential to aid in the development of an effective means by which accommodation for students and essentially any potential rentees can be found and attained.